Yield gap analysis of major pulses in India - Rimal, N. S.; Kumar, S. (Journal of the Institute of Agriculture and Animal Science, 2018)
In order to assess the nature and extent of yield gap in major pulses in India, published data from different official records were used for different time periods and comparison was made between states and India regarding yield difference of different pulses. Yield gap II was assessed with the help of data obtained from annual reports of Indian Institute of Pulses Research, Kanpur for major pulses crops. Both yield gap I and Yield gap II was examined in case of chickpea for the period of 2011-12 taking an aggregated yield data. The result revealed that most of the major pulses growing states were having lower yield of total pulses than national average while minor states showed higher yield during 2006-2012. With the positive growth in yield of individual pulses minor states were moving forward and showed potential increase in production of pulses. Yield gap II of major pulses in India showed an increase in the recent period over 2006-07. In case of chickpea frontline demonstration data for the period of 2011-12 revealed that yield gap II ranged from 7.63% in Karnataka to 24.37% in Madhya Pradesh among major chickpea producing states while this gap was 15.80% in Chattishgarh and 29.09% in Bihar among minor states. Yield gap for the same period was observed to be 28.46% in Madhya Pradesh, 28.75% in Karnataka and 28.56% in Maharashtra. These states contribute more than 50% of area share indicating tremendous untapped potential. Factors causing exploitable yield gap could be managed with effective implementation of government program along with participatory research and extension services ensured within the time frame. Journal of the Institute of Agriculture and Animal Science. Vol. 33-34, 2015, page: 213-219